2015
DOI: 10.1002/fsn3.211
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative responses during germination in quinoa grown in vitamin B‐rich medium

Abstract: Synthetic vitamin preparations have grown in popularity to combat health risks associated with an imbalanced diet, poor exercise and stress. In terms of bioavailability and diversity, they lack behind vitamins naturally occurring in plants. Solutions to obtain plant-derived vitamins at a larger scale are highly desirable. B vitamins act as precursors of enzymatic cofactors, thereby regulating important metabolic processes both in animals and plants. Because during plant germination, the vitamin content and mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…These observations rather pointed to enzymatic activities; and catalase, which uses H 2 O 2 to generate water and oxygen, was the suspect enzyme. Its activities are knowingly high in extracts from dry quinoa seeds ( Pitzschke et al, 2015 ), and in-gel activity assays confirmed this (not shown). If “bubbling” indeed resulted from catalase-mediated oxygen formation one would expect a certain pool of the enzyme’s substrate in seeds.…”
Section: Resultsmentioning
confidence: 84%
“…These observations rather pointed to enzymatic activities; and catalase, which uses H 2 O 2 to generate water and oxygen, was the suspect enzyme. Its activities are knowingly high in extracts from dry quinoa seeds ( Pitzschke et al, 2015 ), and in-gel activity assays confirmed this (not shown). If “bubbling” indeed resulted from catalase-mediated oxygen formation one would expect a certain pool of the enzyme’s substrate in seeds.…”
Section: Resultsmentioning
confidence: 84%
“…However, the presence of these species results in an oxidative stress in the cells. Moreover, the exposure to light also causes stress in the grain inducing the synthesis of antioxidants, for example, ascorbic acid (Pitzschke, Fraundorfer, Guggemos, & Fuchs, 2015).…”
Section: Discussion Of the Effect Of Sprouting Time And Temperaturementioning
confidence: 99%
“…There are at least three SOD isoforms found in seeds. They show high activity, but the literature data indicate also a major contribution of other antioxidant mechanism factors (Pitzschke, Fraundorfer, Guggemos, & Fuchs, 2015).…”
Section: Food Chemistrymentioning
confidence: 96%